(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This study explores innovative approaches to history education that prioritize practical and experiential learning techniques in secondary school classrooms. The research focuses on methods such as source analysis, project-based learning, role playing, and historical simulations to enhance students’ understanding of historical events and processes. By engaging students in hands-on activities and critical inquiry, these methods aim to develop their research competencies, analytical thinking, and ability to interpret historical evidence independently.